Exploring knowledge, perception, and use of surface electromyography in physiotherapy post graduate trainees in Italy: a single center preliminary survey - Bertoni, Gianluca; Leuzzi, Gaia; Job, Mirko; De Simone, Marica; Testa, Marco (Frontiers in Rehabilitation Sciences, 2024)
IntroductionSurface electromyography (sEMG) is a non-invasive technique that records muscle electrical activity using skin-surface electrodes, aiding physiotherapists in assessing and treating muscular and neuromuscular conditions. Despite its potential, sEMG remains underutilized in Italy. This study aims to evaluate Italian physiotherapists’ knowledge and use of sEMG, specifically among those who completed the Master's Degree in Rehabilitation of Musculoskeletal and Rheumatological Disorders at the University of Genoa.MethodsThis cross-sectional study, approved by the University of Genoa's Ethical Committee, utilized an anonymous web survey to gather data from physiotherapy students in the master's program. The survey, developed based on the International Handbook of Survey Methodology, consisted of 12 questions covering demographics, previous sEMG experience, the importance of sEMG in practice and research, and educational satisfaction. Data collection spanned from January to May 2024, with a response rate of 72.7% (93 participants). Descriptive analysis was used to summarize the data.ResultsThe average age of respondents was 26.5 years, with 55.9% being male. Only 3.2% reported using sEMG in their practice. While 46.2% considered sEMG moderately important for practice, 40.9% deemed it extremely important for research. Most participants felt their undergraduate education inadequately prepared them for using sEMG, with 81.7% rating their preparation as insufficient. Although the master's program improved sEMG knowledge, 66.7% indicated no significant proficiency gain.ConclusionItalian physiotherapists view sEMG mainly as a research tool rather than a clinical one. The findings highlight the need for curriculum reforms to enhance both theoretical and practical sEMG education. Simplifying and standardizing sEMG protocols and integrating sEMG training into physiotherapy curricula are essential steps to better prepare clinicians for its clinical application.